CONSUMER BOYCOTTS IN INDONESIA NATIONAL PRESS CONTEXT, 1982-MID 2010: A PRELIMINARY STUDY - Kresno Agus Hendarto (Journal of Management and Business, 2011)
The objective of this study is to describe how boycotts are released in Indonesia national press. The data were obtained from mass media using saturation sampling. Data obtained is analyzed using qualitative content analysis. The results showed that, as in other countries, in Indonesia, boycott has increased in quantity. In the boycott news, the country of origin target is released more than corporate target. Mostly the boycott in Indonesia is sponsored/triggered by groups. In this case, religious groups are the primary cause. In addition there are environmental and worker groups. Although the boycott in Indonesia is mostly intended to express dissatisfaction to particular corporate or country of origin actions, some boycotts are intended to establish social or political control to the boycott target.